2021
DOI: 10.1139/cjps-2020-0067
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between auxins and cytokinins in the growth and organogenesis of Ocimum basilicum L. ‘Grecco a Palla’

Abstract: The in vitro development of a plant is controlled by factors that promote a series of plant responses, which interfere with tissue organogenesis and morphology. For plants of the family Lamiaceae, these factors remain unknown or poorly understood, hindering in vitro cultivation of these plants. The basil cultivar ‘Grecco a palla’ has attractive chemical properties for medicinal, pharmaceutical, and cosmetic industries; however, its production is limited due to the lack of appropriate cultivation conditions. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…These results demonstrated the basil's 'Grecco a Palla' potential in phenol production. One of the factors that can be attributed to this is the root and shoot generation in these treatments since the formation of specialized tissues is a prerequisite for producing these compounds in vegetables (GÓRSKI et al, 2021). The number of phenols is also related to organogenesis regulation in the area, i.e., appropriate development leads to higher phenol rates (JAKOVLJEVIĆ et al, 2022).…”
Section: Gorski Et Almentioning
confidence: 99%
“…These results demonstrated the basil's 'Grecco a Palla' potential in phenol production. One of the factors that can be attributed to this is the root and shoot generation in these treatments since the formation of specialized tissues is a prerequisite for producing these compounds in vegetables (GÓRSKI et al, 2021). The number of phenols is also related to organogenesis regulation in the area, i.e., appropriate development leads to higher phenol rates (JAKOVLJEVIĆ et al, 2022).…”
Section: Gorski Et Almentioning
confidence: 99%
“…The disorder was observed in basil, lavender, and sage treated with excess BAP, although the exact cause of hyperhydricity remains unknown. Some reports indicated that BAP possibly causes cell hypertrophy in plants (ZUZARTE et al, 2010;GÓRSKI;GEROTTI;MAGALHÃES, 2021;JAN et al, 2021).…”
Section: Germination and Physiological Disorders Induced By Pgrsmentioning
confidence: 99%